Buccal space malignant solitary fibrous tumour: a case report - Chandrapattan, Prathamesh; Panda, Sangram Keshari; Agrawal, Sunil; Sahoo, Pradyuman Kumar (International Surgery Journal, 2022)
Solitary fibrous tumour (SFT) occurs rarely in extrapleural sites such as head and neck region. Head and neck region is affected in 16% cases occurring usually in orbit and paranasal region and are benign variants. Though usually benign, Malignant SFT in buccal space is extremely rare and comes with challenges in diagnosis and management. We report a rare case of Malignant SFT in the buccal space in a 70-year-old- gentleman who presented with slow growing mass in left cheek. Patient was treated with surgical excision and adjuvant radiotherapy and is on regular follow up. Malignant SFTs are difficult to diagnose due to lack of specific histological pattern but certain IHC and genomic markers can help. Buccal space malignant SFT can be managed by wide local excision and adjuvant radiotherapy in cases of large tumour size and margin positive resection.